Limitations in the screening of potentially anti-cryptosporidial agents using laboratory rodents with gastric cryptosporidiosis - Valigurova, Andrea; Peckova, Radka; Dolezal, Karel; Sak, Bohumil; Kvetonova, Dana; Kvac, Martin; Nurcahyo, Wisnu; Foitova, Ivona (Folia parasitologica, 2018)
The emergence of cryptosporidiosis, a zoonotic disease of the gastrointestinal and respiratory tract caused by Cryptosporidium Tyzzer, 1907, triggered numerous screening studies of various compounds for potential anti-cryptosporidial activity, the majority of which proved ineffective. Extracts of Indonesian plants, Piper betle and Diospyros sumatrana, were tested for potential anti-cryptosporidial activity using Mastomys coucha (Smith), experimentally inoculated with Cryptosporidium proliferans Kváč, Havrdová, Hlásková, Daňková, Kanděra, Ježková, Vítovec, Sak, Ortega, Xiao, Modrý, Chelladurai, Prantlová et McEvoy, 2016. None of the plant extracts tested showed significant activity against cryptosporidia; however, the results indicate that the following issues should be addressed in similar experimental studies. The monitoring of oocyst shedding during the entire experimental trial, supplemented with histological examination of affected gastric tissue at the time of treatment termination, revealed that similar studies are generally unreliable if evaluations of drug efficacy are based exclusively on oocyst shedding. Moreover, the reduction of oocyst shedding did not guarantee the eradication of cryptosporidia in treated individuals. For treatment trials performed on experimentally inoculated laboratory rodents, only animals in the advanced phase of cryptosporidiosis should be used for the correct interpretation of pathological alterations observed in affected tissue. All the solvents used (methanol, methanol-tetrahydrofuran and dimethylsulfoxid) were shown to be suitable for these studies, i.e. they did not exhibit negative effects on the subjects. The halofuginone lactate, routinely administered in intestinal cryptosporidiosis in calves, was shown to be ineffective against gastric cryptosporidiosis in mice caused by C. proliferans. In contrast, the control application of extract Arabidopsis thaliana, from which we had expected a neutral effect, turned out to have some positive impact on affected gastric tissue.
Keywords: pathology; Piper betle; gastric; Plant Extracts; Drug Evaluation, Preclinical; Animals; Murinae; preklinické hodnocení léčiv; Diospyros; Cryptosporidium; Coccidiostats; Cryptosporidiosis; oocyst; kryptosporidióza; treatment; rostlinné extrakty; kokcidiostatika; zvířata